ANALISIS KESEDIAAN MEMBAYAR (WILLINGNESS TO PAY) SUMBERDAYA AIR DAERAH ALIRAN SUNGAI WANGGU BAGIAN TENGAH - Ahmaliun, La De; Arafah, Nur; Bana, Sahindomi; Alwi, La Ode; Laksananny, Satya Agustina; Arniawati, Arniawati; Sakti, Abdul; Fitriani, Dewi; Gandri, La; Qadri, Muhammad Saleh; Putri, Sarwinda Intan (MAKILA, 2024)
The Wanggu Watershed is one of the water resources providers in the Southeast Sulawesi region and is part of the Wanggu Watershed community life. This research aims to identify. This study aims to determine the Willingness To Pay value (WTP) of the Wanggu Sub Watershed as the cost of maintaining water sources. The location of this study is within the central Wanggu watershed area. The sampling method is carried out by Purposive Sampling and Convenience Sampling methods at the same time. The respondents were 54 people, including farmers, fishermen, traders, and entrepreneurs using water sources around the Wanggu watershed. Respondents' backgrounds include characteristics of gender, age, education level, and type of work. This study result showed that the willingness to pay (WTP) value obtained from using the water resources of Wanggu Sub Watershed from the Lepo-Lepo Village community is Rp. / year from the Watubangga Village community.